Asian development outlook (ADO) 2019 update fostering growth and inclusion in Asia's cities. (Mandaluyong City, Metro Manila Asian Development Bank, 2019)
Growth in developing Asia is moderating but remains robust. As global trade slows and investment weakens, regional growth forecasts are trimmed from Asian Development Outlook 2019 by 0.3 percentage points for 2019 and by 0.1 points for 2020 compared to April forecasts. The revisions reflect gloomier prospects for international trade and evidence of slowing growth in the advanced economies and the People Republic of China, as well as in India and the larger economies in East and Southeast Asia.
Keywords: Economics; Urban development